Experiences of nurses working in nurse‐led clinics in Traditional Chinese Medicine hospitals: A focused ethnographic study. Issue 2 (19th August 2022) - Dong, Zhaoyang; Wei, Lin; Sun, Xinglan; Xiang, Jiagen; Hu, Yanan; Lin, Meizhen; Tan, Yibing
Abstract: Background: Traditional Chinese Medicine (TCM) nurse‐led clinics (NLC) is an innovative working model in China, representing the specialization and extension of nurses' role. However, as a pioneer in TCM nursing, this new model of working is facing both opportunities and challenges because it is known little about the operational status of NLCs. Aims: To explore the experiences of nurses who work in NLC in TCM hospitals. Materials & Methods: A focused ethnographic study was conducted in three TCM hospitals affiliated with Guangzhou University of Chinese Medicine. We interviewed eleven nurses in those hospitals and observed seven of them working with patients. We used snowball sampling for data collection including interview, non‐participant observation and documents from medical records. All the data were processed as following steps: (a) coding for descriptive labels; (b) sorting for patterns; (c) identifying outliers or negative cases; (d) generalizing with construction and theories and (e) noting reflective remarks. Results: Nurse‐led clinics help nurses develop their skills and knowledge that are highly recognized by public since they meet the growing needs of patients and also relieve the workload of physicians in the hospitals. However, lack of specialization is still a major challenge in NLCs due to insufficiency of full‐time staff with specialized education, nurse‐led practice without standardized guidelines, restrictions on prescription right of nurses, and also inadequate support from hospitals. Discussions: As a revolutionary innovation of working model for nurses in TCM hospitals, NLCs could improve quality of care and lead to a comprehensive promotion of nursing career. However, there are several challenges on providing high quality care for patients whilst improving educational development of nurses. This study suggests that nurses, hospital administration and the government should cooperate with each other to develop standard nursing programs for NLCs. Conclusions: It is imperative to identify nursing roles, collect available resources, and develop supportive policies and training programs to enhance the quality of NLCs.